Contagious Migration: Evidence from the Philippines - Michael Ralph M. Abrigo; Desiree A. Desierto (Philippine Institute for Development Studies (PIDS), 2011)
Outward migration data from the Philippines exhibit spatial clustering. This is likely due to information spillover effects - fellow migrants share information with other neighboring migrants, thereby lowering the costs of migration. To verify this, we use spatial econometrics to define a geography-based network of migrants and estimate its effect on the growth in the number of succeeding migrants. We find that current and past migration from one municipality induces contemporaneous and future migration in neighboring municipalities.
Keywords: C21; D85; F22; 330; migration; Philippines; fiduciary system; global imbalances; network effects; spatial econometrics; Auswanderung; Soziales Netzwerk; Spillover-Effekt; Migranten; Motivation; Philippinen